2004
DOI: 10.1002/ajmg.a.30160
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomere FISH in 50 children with mental retardation and minor anomalies, identified by a checklist, detects 10 rearrangements including a de novo balanced translocation of chromosomes 17p13.3 and 20q13.33

Abstract: Submicroscopic or subtle aneusomies at the chromosome ends, typically diagnosed by subtelomere fluorescence in situ hybridization (FISH), are a significant cause of idiopathic mental retardation (MR). Some 20 subtelomere studies, including more than 2,500 subjects, have been reported. The studies are not directly comparable because different techniques and patient ascertainment criteria were used, but an analysis of 14 studies showed that aberrations were detected in 97 out of 1,718 patients (5.8%, range 2-29%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…It is reasonable to assume that different detection rates are due to selection criteria, and it is likely that stringent selection criteria like the 5-item checklist (family history of MR, prenatal onset growth retardation, postnatal growth abnormalities, facial dysmorphic features, non-facial dysmorphism and/or congenital abnormalities) provided by de Vries et al [16] will increase the detection yield of chromosome abnormalities. This can also be seen in the study reported by Walter et al [17], where the authors have performed a subtelomere FISH study of 50 unrelated children ascertained by a checklist that evaluates MR or development delay, dysmorphism, growth defect, and abnormal pedigree and found ten causal rearrangements (detection rate of 20%).…”
Section: Discussionsupporting
confidence: 53%
“…It is reasonable to assume that different detection rates are due to selection criteria, and it is likely that stringent selection criteria like the 5-item checklist (family history of MR, prenatal onset growth retardation, postnatal growth abnormalities, facial dysmorphic features, non-facial dysmorphism and/or congenital abnormalities) provided by de Vries et al [16] will increase the detection yield of chromosome abnormalities. This can also be seen in the study reported by Walter et al [17], where the authors have performed a subtelomere FISH study of 50 unrelated children ascertained by a checklist that evaluates MR or development delay, dysmorphism, growth defect, and abnormal pedigree and found ten causal rearrangements (detection rate of 20%).…”
Section: Discussionsupporting
confidence: 53%
“…TRPV1 knockout mice reveal changes in behavior and LTD (Marsch et al, 2007; Gibson et al, 2008;Kauer and Gibson, 2009). In humans, a mutation has been described potentially affecting TRPV1 and/or TRPV3 through a de novo balanced chromosomal translocation (Walter et al, 2004). Clinical features of this mutation include an increased head size, severe speech and vision defects, and mental retardation (MR), a phenotype potentially caused by deficits in neuronal development.…”
mentioning
confidence: 99%
“…These data qualify BACs 384D8 and 799F10 for subtelomere FISH studies of chromosome 22q. 20 The phenotypes of partial trisomy 22q include the CES, the der(22) syndrome, 10 the microduplication 22q11.2 syndrome, 32 and the chromosome 22q duplication syndrome/s. Full trisomy 22 typically results in abortion, but partial 22q trisomy including the distal chromo some 22q11.2 and/or parts of 22q12 -q13 was reported with phenotypes that were compatible with survival: the chromosome 22q duplication syndrome/s.…”
Section: Discussionmentioning
confidence: 99%
“…21 Table 2 provides properties of the probes and the order of location from 22pter. After preselecting 20 BACs from the CTA library based on their size and location on the human chromosome 22q 21 and testing each clone using FISH on 25 normal controls, we selected 12 BACs (including the previously described clones 678G6, 201C11, 219G6, 384D8, and 799F10) 19,20 that showed clear FISH signals, no variation of hybridization at normal 22s, and no second sites at other chromosomes. Cosmid/BAC DNA was amplified using a degenerate oligonucleotide primed shuttle polymerase chain reaction (DOP-shuttle-PCR) protocol.…”
Section: Fishmentioning
confidence: 99%